Pemberdayaan Masyarakat Berbasis Lingkungan Melalui Penataan Lahan Kosong untuk Apotik Hidup di Hutan Kota Giong Siu Mataram - Husnul Jannah; Iwan Desimal; Nita Erista; Baiq Muli Harisanti; Nurtajudin Nurtajudin; Sri Nopita Primawati (Jurnal Pengabdian UNDIKMA, 2023)
This service aims to empower the community around the Giong Siu City Forest, both visitors and managers, by arranging empty land for a live dispensary. The method of implementing this service included socialization and practice with a participatory approach. The results of this service activity showed that visitors and managers were very enthusiastic about participating in the socialization activity until completion. Medicinal plant planting activities were carried out together with the manager. Medicinal plants planted include yellow turmeric, white turmeric, ginger, galangal, galangal, aloe vera, and lavender. This planting was carried out in the Giong Siu location, which was still empty, so that optimal light was obtained and was close to a water source for watering.